Temperature Gradient: A Simple Method for Single Crystal Growth - Anh Tuan, Duong; Thanh Huong, Nguyen Thi; Thi Minh Hai, Nguyen; Anh Tuan, Pham; Thi My Hao, Dinh; Cho, Sunglae (VNU Journal of Science: Mathematics - Physics; Vol 35 No 1, 2019)
Abstract: In this article, we provide a simple method for the growth of bulk single crystalline. By the control temperature along a vertical furnace, we can easily fabricate bulk single crystals. This technique is called the temperature gradient method. To create a temperature gradient along the body of the furnace, the density of resistance wire which is coiled along the body of furnace is different. The density increases from the bottom to the top of the furnace. So that, at any time of the growing process, the temperature at the bottom of furnace is the smallest. During could down process, single crystal in the ampoule has been grown up from a seed at the bottom. Using this method, we successfully grew layer structure single crystals such as SnSe, SnSe 2 , SnS, GaTe, InSe 2 , GaSe. X-ray diffraction and FE-SEM measurements indicated the high quality of single crystals. By changing cooling speed, we can control the number of defects in the single crystals. Keywords: Temperature gradient method, single crystal growth, layer structure materials.